Keep and Give Away : Poems - Meyers, Susan, 1945-2017 (Book collections on Project MUSE., 2006)
Keep and Give Away was selected by Terrance Hayes as the inaugural winner of the South Carolina Poetry Book Prize sponsored by the South Carolina Poetry Initiative. In her first full-length collection, Susan Meyers guides us through her examination of life's ordinary moments and the seemingly ordinary images that abide in them to reveal the extraordinary. From minutia to marriage, crumbs to crows, nothing is too commonplace to escape her attention as she traverses terrains of childhood, loss, relationships, and death. Mostly lyrical and often elegiac, the poems of Keep and Give Away move along the rifts between the past and present, the lived and desired. The dominant emotions of the verses are deepened by observations rooted in our natural world, where birds are "yeses quickening the air" and the sky can "lap you up, and up." In the book's final section, marriage poems turn to fishing and gardening for their truths, contemplations that recognize the realities of a world governed by luck, imperfection, contraries, and-most of all-love